Development of Physical Education Teacher Education in Hong Kong - A Problem Setting Analysis: 香港體育師資培訓的發展及探索 - LI, Chung (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Ever since Physical Education (PE) became one of electives in the Teacher Education (TE) programme in 1947, it has gradually developed from a practical and professional oriented subject to a theoretical and academic based discipline in the tertiary institutes in Hong Kong. This paper described the ’selected’ historical incidents of the development of PETE in Hong Kong. PETE becomes hegemonic towards scientific bias, health-dominated, technocratic and utilitarian-oriented nowadays. It creates tensions of dichotomised issues between PE and sports science; PE and medical science; theoretical and pedagogical orientation; research and practical basis; scholarly and professional discipline; and technocratic and inquiry focus etc. Its development illustrates the differences in directions, status, functions and practices. It intents to identify problems of the present practices and to initiate discussion on alternative directions of the PETE in the coming future. 香港的體育師資培訓隨著時代的轉變而發展出不同的配套。本文就其歷史、發展、本質及任務帶引出討論及分析，內容包括體育與運動科學、體育理論與敎學、體育研究及專業地位等等；藉此提出理想方向的探索。